A hospital-based clinical study of childhood psoriasis in a tertiary care center of Northeast India - Seujee Das; Pankaj Adhicari (Wolters Kluwer Medknow Publications, 2018)
Background: Childhood psoriasis has been reported to differ from that among adults. There are a limited number of studies on childhood psoriasis and none from the north-eastern part of India. A detailed clinical study will help to understand better the disease profile in children, thereby assisting in better diagnosis and treatment. Objective: The objective of this study was the clinical profile of childhood psoriasis. Materials and Methods: The present observational study was conducted in the Dermatology Outpatient Department of Assam Medical College and Hospital, Dibrugarh, during 12 months from June 2014 to May 2015. All children up to 13 years presenting with psoriasis during 1 year were taken as study participants after obtaining the written consent from the sole guardian. A detailed examination and relevant investigations were done, whenever necessary. The findings were recorded in a pro forma for the analysis and interpretation of data. Results: A total of 26 cases of childhood psoriasis were recorded during the study. The prevalence of childhood psoriasis in our outpatient pediatric population was 1.24%. Female cases (19; 73.08%) outnumbered male cases (7; 26.92%). A maximum number of cases were noted in 9-13 years of age group. The lower extremities (11; 42.31%) were the most common site of onset. Plaque type (14; 53.85%) was found to be the most common type. About 7.69% cases had a positive family history. Conclusion: Frequent involvement of soles was noted in childhood psoriasis similar to other parts of India but unlike other parts of the world. Pediatric patients had significantly more involvement of the trunk, face, and groin than did adult patients.